Cosmogenic10Be and OSL dating of marine terraces along the central-east coast of korea: Spatio-temporal variations in uplift rates - Lee, S.Y.; Seong, Y.B.; Kang, H.C.; Choi, K.H.; Yu, B.Y. (Bentham Science Publishers B.V., 2015)
We report the abandonment age of the Jeongdongjin (JDJ) coastal terrace that lies at 65 m a.s.l. The age of the JDJ terrace surface has yet to be equivocally constrained because of its antiquity (>MIS 5), challenging the application of conventional radiocarbon and optically stimulated luminescence (OSL) dating techniques. The reliability of applied indirect age constraints on the sediments by amino-acid racemization and tephra chronology is debated. We present the first application of cosmogenic surface exposure dating to constrain the age of the old terrace in Korea. We dated four samples from the paleo shore platform surface using cosmogenic10Be surface exposure dating techniques. The analyses yielded exposure ages ranging from 240 to 170 kyr and likely correspond to the penultimate interglacial period (MIS 7). Sandy beach sediments overlying marine terraces at nearby Anin (~23 m a.s.l.) and Ayajin (~17 m a.s.l.) were dated by OSL. OSL dating of terrace beach sand in two separate areas yielded ages between 129-117 and 70-66 kyr, interpreted MIS 5e and MIS 5a, respectively. Combining the exposure ages and the heights of terraces corrected for paleo sea level, we obtain uplift rates of 353 for JDJ, 159 for Anin, and 238 mm/kyr for Ayajin. The results indicate spatio-temporal variations in the rate of surface uplift along the east coast of Korea during the late Quaternary. Furthermore, the west and east coasts of central Korea experienced different uplift histories during the late Quaternary, possibly resulting from the effects of different tectonic regimes. ？ Lee et al.